Photoresist ink
By using photoresist ink containing zirconia powder in a silicone matrix on the COB packaging substrate of deep ultraviolet LED, the lack of reflectivity and resistance of deep ultraviolet LED substrates in the prior art is solved, and the high reflectivity and resistance are improved, and the luminescence efficiency and sterilization effect of deep ultraviolet rays are enhanced.
Patent Information
- Application Number
- CN202180006773.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-20
- Filing Date
- 2021-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-07
AI Technical Summary
The prior art is difficult to achieve high reflectivity and resistance on the COB packaging substrate for deep ultraviolet LEDs, especially in the wavelength region of 250 nm to 280 nm, which affects the luminescence efficiency and sterilization effect of deep ultraviolet rays.
Use a photoresist ink containing zirconia powder in a silicone matrix, and use precision dispersion of zirconia powder to ensure that its average particle size D50 is less than 1 μm, and an appropriate amount of inorganic powder, such as aluminum oxide, is added to the photoresist ink to improve the reflectivity and resistance of deep ultraviolet rays.
It achieves a high reflectivity of more than 85% in the deep ultraviolet wavelength region between 250nm and 280nm, and maintains good resistance after long-term exposure to deep ultraviolet rays, improving the luminous efficiency and sterilization effect of deep ultraviolet LEDs.
Smart Images

Figure CN114762135B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photoresist ink that can be used as a protective film (high-reflection insulating film) for a substrate for a deep ultraviolet LED, and in particular to a photoresist ink that diffusely reflects deep ultraviolet rays with good efficiency. Background Art
[0002] Compared to so-called UVA light with a wavelength of 320nm to 400nm and so-called UVB light with a wavelength of 280nm to 320nm, deep ultraviolet light with a wavelength of 250nm to 280nm or less has very high energy and is highly expected to be a light that can sterilize bacteria or viruses such as Escherichia coli, bacteriophages, and Pseudomonas aeruginosa and purify water or air (Non-Patent Document 1). In particular, previous studies have revealed that deep ultraviolet light of 265nm has a high sterilization ability (Non-Patent Document 2).
[0003] Although mercury lamps and halogen lamps are used as deep ultraviolet light sources, these lamps are large and consume a lot of power, which is why they cannot be widely used in consumer products. Therefore, it is necessary to switch to LED light sources that are small and consume less power.
[0004] Deep UV LED lamps used to purify water or air require a large area to be irradiated at one time, so a so-called chip on board (COB) package is used, in which multiple deep UV LED chips are arranged on a substrate. Here, compared with visible light LEDs, deep UV LED chips have lower luminous efficiency and higher heat generation. Therefore, the substrate used for COB packaging must be a material with high heat dissipation.
[0005] As materials with high heat dissipation, metal substrates such as aluminum or copper or ceramic substrates such as aluminum nitride can be listed. However, since metal substrates are conductive, an insulating film needs to be coated on the surface in order to install deep ultraviolet LED chips. On the other hand, although aluminum nitride substrates have good insulation and can install deep ultraviolet LED chips without coating an insulating film, they are prone to degradation caused by deep ultraviolet rays. Therefore, whether it is a metal substrate or a ceramic substrate, as a COB packaging substrate that will not deteriorate due to deep ultraviolet rays, a protective film must be formed on the surface. And this protective film is required to be a highly reflective insulating film that has both insulation and high reflectivity to deep ultraviolet rays.
[0006] As such a protective film material, a photoresist ink based on silicone and containing inorganic fillers that is not easily degraded under deep ultraviolet irradiation is known (Patent Document 1, Patent Document 2). However, the diffuse reflectivity of the photoresist ink disclosed here in the deep ultraviolet wavelength region is very low, which does not help to improve the luminous efficiency of deep ultraviolet LEDs. Patent Document 3 also discloses a deep ultraviolet substrate using glass ceramics. Although this substrate has heat dissipation properties due to heat dissipation vias, its reflectivity at 280nm is about 75%, which is difficult to say that it has sufficient reflectivity even compared with substrates used for visible light LEDs (Patent Document 4, Patent Document 5).
[0007] Patent document 6 discloses an LED module, wherein the reflective layer as at least a part of the substrate is a layer including a binder matrix and inorganic particles dispersed in the binder matrix, and discloses that at least one of the inorganic particles can be selected from a group consisting of aluminum oxide, zirconium oxide, titanium oxide, and barium oxide, and further discloses that the average particle size of the inorganic particles is 0.1 μm or more and 50 μm or less. However, Patent document 6 only records the reflectivity at a wavelength of 360 nm or more, and does not record or teach the reflectivity at a wavelength of 250 nm to 280 nm, or whether it has deep ultraviolet resistance.
[0008] Further evaluating Patent Document 6, although the applicant recorded in the claim that the average particle size of the inorganic particles is in a very wide range of not less than 0.01 μm and not more than 50 μm, the specification only indicates that the average particle size of the inorganic particles ZrO2 is 2.0 μm, and the reflectivity of 360nm to 740nm when the content of ZrO2 particles is 64 volume %, and the rest can be considered to be used for adjusting the surface roughness Ra.
[0009] [Prior art literature]
[0010] 〔Patent Document〕
[0011] [Patent Document 1] Japanese Patent Application Publication No. 2012-227292
[0012] [Patent Document 2] WO2011 / 118108
[0013] [Patent Document 3] Japanese Patent Application Publication No. 2017-117982
[0014] [Patent Document 4] Japanese Patent Application Publication No. 2011-246329
[0015] [Patent Document 5] Japanese Patent Application Publication No. 2014-187158
[0016] [Patent Document 6] Japanese Patent Application Publication No. 2019-125683
[0017] [Non-patent document 1] https: / / www.ultraviolet-led.com / media / japanese / a21
[0018] [Non-patent document 2] Water Research 130 (2018) 31-37 Summary of the invention
[0019] [Problems that the invention aims to solve]
[0020] With the increasing demand for improved safety in water or air purification, there will be a strong demand for improved efficiency of deep ultraviolet LEDs with wavelengths of 265nm, 254nm, 270nm and 280nm, which have excellent sterilization effects. Therefore, a photoresist ink is sought that has little degradation due to deep ultraviolet rays and can be used as a protective film for COB packaging substrates with high reflection at these wavelengths.
[0021] [Technical means to solve the problem]
[0022] The present invention provides a photoresist ink which is less degraded by deep ultraviolet rays and has high reflectivity in the wavelength region of 250nm to 280nm with high bactericidal effect, and is particularly suitable as a protective film for a substrate for COB packaging.
[0023] In order to solve the above-mentioned problems, the photoresist ink of the present invention contains silicone and zirconium oxide powder as essential components.
[0024] Silicone is not particularly limited, but preferably has a viscosity of 10 Pa·s or less at the operating temperature (normal temperature) for dispersing zirconium oxide powder. If the viscosity exceeds 10 Pa·s, the viscosity may increase during mixing with zirconium oxide powder. If the viscosity increases during mixing, the zirconium oxide powder may not be well dispersed, and the deep ultraviolet reflectivity may decrease.
[0025] In order to reduce the siloxane gas generated during the coating and curing step of the COB packaging substrate, it is better to use refined silicone. If unrefined silicone is used, siloxane gas will be generated. If the siloxane gas adheres to the contact of the LED component, the decomposed component silicon dioxide (SiO2) will act as a current insulator and cause poor contact problems.
[0026] In the present invention, the average particle size D50 of the zirconium oxide powder is less than 1 μm, and its content must be between 32 wt% and 50 wt%. In addition, it is known that when the film thickness of the photoresist ink after curing is more than 30 μm, it can exhibit a high reflectivity of more than 85% in the wavelength region of 250 nm to 280 nm of deep ultraviolet rays with a high bactericidal effect.
[0027] In the present invention, it is known that when the average particle size D50 of the zirconium oxide powder exceeds 1 μm, a long wavelength shift of the reflection wavelength band occurs, and the reflectivity at 250 nm decreases. It is necessary to select a particle size within a range where the average particle size D50 is less than 1 μm and can be uniformly dispersed in silicone (without aggregation). Experience has shown that aggregation is likely to occur if the average particle size is less than 0.2 μm.
[0028] The content of zirconium oxide powder must be 32wt% or more. If it is less than 32wt%, the reflectivity of deep ultraviolet light will decrease. On the other hand, if it exceeds 50wt%, the zirconium oxide powder will begin to aggregate, and the reflectivity of deep ultraviolet light at 250nm will decrease.
[0029] The particle shape of the zirconium oxide powder is not particularly limited, but generally speaking, particles with a shape close to spherical are preferred over irregular particles because they can reduce the specific surface area and increase the amount added.
[0030] As the inorganic powder added, although zirconium oxide powder is an essential component, other inorganic powders can also be appropriately added. At this time, inorganic powders such as titanium oxide that absorb ultraviolet rays will cause the reflectivity of deep ultraviolet rays to decrease. Therefore, it is necessary to use inorganic powders that do not have an absorption region for ultraviolet rays. As such an inorganic powder, aluminum oxide can be cited. The particle size of the inorganic powder added is preferably the same as that of zirconium oxide powder, with an average particle size D50 of 1 μm or less. This is to prevent the reflectivity in the wavelength region of 250nm to 280nm from decreasing.
[0031] As a method of applying the photoresist ink of the present invention to a COB packaging substrate, commonly known screen printing, dispensing, spray printing, etc. can be used. As for the thickness of the printed film, in order to achieve the high reflectivity in the wavelength region of 250nm to 280nm as mentioned above, it must be 30μm or more.
[0032] 〔Comparison with the efficacy of prior art〕
[0033] According to the present invention, a photoresist ink can be provided, which has a diffuse reflectivity of more than 85% in the deep ultraviolet wavelength region of 250nm to 280nm. Even if it is irradiated with deep ultraviolet rays for a long time, there will be no significant deterioration such as a decrease in deep ultraviolet reflectivity or a change in color tone, and it has excellent deep ultraviolet resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A diagram showing a COB package with a deep ultraviolet LED chip mounted on it.
[0035] Figure 2 Schematic diagram of a deep ultraviolet protective film (deep ultraviolet high reflective insulating film) formed by the photoresist ink of the present invention.
[0036] Figure 3 The present invention is an example of the reflection spectrum from the ultraviolet region to the visible light region of the deep ultraviolet protective film on the glass substrate (sample No. 2) and the deep ultraviolet protective film on the aluminum substrate formed by the photoresist ink of the present invention.
[0037] Figure 4 This is an example of the reflectance spectrum in the ultraviolet region of a deep ultraviolet protective film formed on a glass substrate using the photoresist ink of the present invention (sample No. 2).
[0038] Figure 5 This is another example (samples No. 16 and No. 17) of the reflectance spectrum in the ultraviolet region of the deep ultraviolet protective film on the glass substrate formed with the photoresist ink of the present invention. DETAILED DESCRIPTION
[0039] The present invention will be specifically described below with reference to Examples, but the present invention is not limited thereto.
[0040] As silicone, condensed polydimethylsiloxane (PDMS) was used, and as a curing agent for curing silicone, dioctyltin (Nitto Kasei Co., Ltd.) was used.
[0041] Zirconia powders sold by Daiichi Kokuzo Chemical Industry Co., Ltd. or Shin Nippon Electric Industries, Ltd. were used according to the average particle size. Products with average particle sizes D50 of 0.5 μm, 1 μm, 2 μm, 3 μm, and 14 μm were used to compare their deep ultraviolet reflectivity.
[0042] The photoresist ink with an average particle size D50 of 0.5 μm or 1 μm was used as the zirconium oxide powder. 60 wt% of PDMS, 35 wt% of zirconium oxide powder and 5 wt% of solvent were mixed by a centrifugal mixer (ARE-310 manufactured by THINKY), and then precisely dispersed by a three-roll mill (three-roll mill manufactured by Inoue Seisakusho). The roller gap of the three-roll mill was set to 15 μm for precise dispersion. In addition, Texanol was used as a solvent.
[0043] The photoresist ink using zirconium oxide powder with an average particle size D50 of 2 μm, 3 μm or 14 μm is prepared by mixing 62 wt% PDMS, 36 wt% zirconium oxide powder and 2 wt% solvent (Texanol) by a centrifugal mixer and then precisely dispersing it by a three-roll mill. The roller gap of the three-roll mill is set to 15 μm.
[0044] Photoresist inks with different zirconium oxide powder contents were prepared under the following conditions. Using zirconium oxide powder with an average particle size D50 of 0.5 μm, (60+X) wt% PDMS, (35-X) wt% zirconium oxide powder and 5 wt% solvent (Texanol) were mixed by a centrifugal stirrer and then finely dispersed by a three-roll mill. The roller gap of the three-roll mill was set to 15 μm. At this time, X was set to 0.3 and 5.
[0045] Sample No. 16, which has a zirconium oxide powder content of 37%, uses zirconium oxide powder with an average particle size D50 of 0.5 μm, and mixes 58 wt% of PDMS, 37 wt% of zirconium oxide powder, and 5 wt% of solvent (Texanol) by a centrifugal agitator, and then precisely disperses them with a three-roll mill. Here, the roller gap of the three-roll mill is set to 15 μm. Sample No. 17, which has a zirconium oxide powder content of 50 wt%, uses zirconium oxide powder with an average particle size D50 of 0.5 μm, and mixes 43 wt% of PDMS, 50 wt% of zirconium oxide powder, and 7 wt% of solvent (Texanol) by a centrifugal agitator, and then precisely disperses them with a three-roll mill. Here, the roller gap of the three-roll mill is set to 15 μm.
[0046] Next, a photoresist ink with zirconium oxide powder and other inorganic powders added is prepared under the following conditions. Using zirconium oxide powder with an average particle size D50 of 0.5 μm, 35 wt% of zirconium oxide powder, (60-Y) wt% of PDMS, Y wt% of inorganic powder and 5 wt% of solvent (Texanol) are mixed by a centrifugal agitator, and then precisely dispersed by a three-roll mill. The roller gap of the three-roll mill is set to 10 μm. At this time, Y is set to 30 and 20. Titanium oxide (Ti-Pure R-101 manufactured by Chemours Co., Ltd.) and aluminum oxide (AL-S43B manufactured by Sumitomo Chemical or AL-45-A manufactured by Showa Denko) are used as inorganic powders.
[0047] (Coating on substrate)
[0048] 1 wt% of hardener (dioctyltin (Nitto Chemical Co., Ltd.)) was added to the photoresist ink, and the #325 screen was used to print on the glass substrate by screen printing. The number of printed layers was changed to adjust the film thickness. After printing, the glass substrate with a deep ultraviolet high reflection protective film coated with the photoresist ink was hardened at 180°C for 2 hours.
[0049] (Deep UV resistance)
[0050] The ultraviolet light with a wavelength of 265nm was adjusted to 37mW / cm 2, irradiated for 1000 hours. The reflectivity change at a wavelength of 265 nm was measured before and after irradiation.
[0051] (Measurement of reflectivity)
[0052] The deep ultraviolet reflective substrate produced and the substrate after ultraviolet irradiation were measured for deep ultraviolet reflectivity using a spectrophotometer. Spectralon (manufactured by Labsphere) was used as a base, and diffuse reflectivity was measured using an integrating sphere.
[0053] The reflectivity of the high reflective substrate obtained by coating the photoresist ink made of zirconium oxide powder with different particle sizes D50 (the content in each condition is 32wt%) and crosslinking and curing is shown in Table 1. The deep ultraviolet reflectivity when the coating film thickness is changed under the condition of particle size of 0.5μm is also shown. From Table 1, it can be seen that the reflective substrate obtained by coating and crosslinking zirconium oxide powder with a particle size of less than 1μm can obtain a high reflectivity of more than 85% in the wavelength range of 250nm to 280nm, except for the condition of less than 30μm film thickness (sample No.1). It is also known that although a reflectivity of more than 85% can be obtained with a film thickness of 30μm, the reflectivity can be increased by further increasing the film thickness. If 100μm is coated (sample No.4), a reflectivity of more than 90% is shown in the wavelength range of 250nm to 280nm. On the other hand, it was found that when the average particle size of the zirconium oxide powder exceeded 1 μm, the reflectance particularly on the short wavelength side (250 nm) dropped sharply (Sample No. 6 to Sample No. 12).
[0054]
Table 1
[0055]
[0056] The reflectance of deep ultraviolet reflective substrates obtained by coating and crosslinking photoresist inks with different zirconium oxide powder contents is shown in Table 2. It is found that when the zirconium oxide powder content is 32 wt % or more, a high reflectance of 85% or more can be obtained in the wavelength range of 250 nm to 280 nm.
[0057]
Table 2
[0058]
[0059] The reflectivity of the high-reflective substrate obtained by coating and cross-linking a photoresist ink made by mixing zirconium oxide powder and other inorganic powders is shown in Table 3. The deep ultraviolet reflectivity of the sample containing titanium oxide powder is greatly reduced. This is due to the absorption of ultraviolet rays by titanium oxide. It is known that the substrate containing aluminum oxide powder can obtain a high reflectivity of more than 85% in the wavelength range of 250nm to 280nm only when using powder with an average particle size D50 of 0.8μm.
[0060]
Table 3
[0061]
[0062] The evaluation results of deep ultraviolet resistance are shown in Table 1. Deep ultraviolet resistance was evaluated by adjusting the ultraviolet light with a wavelength of 265 nm to 37 mW / cm 2 , irradiated for 1000 hours, and measured the change in reflectivity at a wavelength of 265nm before and after irradiation. In the sample (No.12) using large particles with an average particle size of 14μm as zirconium oxide powder, although the reflectivity increased, the reason is unknown. In addition, the changes in samples No.2, No.5, No.6 and No.10 were all about 4%. The reflectivity of samples No.2 and No.5 at 265nm after irradiation was more than 85%.
[0063] As described above, a photoresist ink having high diffuse reflectivity in the deep ultraviolet wavelength region of 250 nm to 280 nm and excellent deep ultraviolet resistance is applied to produce a glass substrate having a protective film having high reflectivity in the deep ultraviolet region.
[0064] Figure 1 The COB substrate with deep ultraviolet LED chips 3 mounted thereon is shown. The deep ultraviolet LED chips 3 are arranged in four rows by means of gold wires 4, and can irradiate a wide range of deep ultraviolet rays. The deep ultraviolet rays irradiated from the rear are reflected to the front without being penetrated or absorbed by the protective film 5 (highly reflective insulating film) formed by the photoresist ink of the present invention, thereby increasing the amount of deep ultraviolet rays.
[0065] Figure 2 This is an enlarged view of a protective film 5 (highly reflective insulating film) formed using the photoresist ink of the present invention, wherein zirconium oxide powder 8 of a specified particle size is dispersed in a silicone matrix 7 at a specified content. The thickness of the protective film 5 (highly reflective insulating film) is greater than 30 μm. When the protective film is formed on a glass substrate, it is translucent in the visible light region (visually).
[0066] Figure 3 The reflectance of sample No. 2 in a wide range from the deep ultraviolet region to the visible light region is shown (solid line). It is known that compared with the reflectance of about 70% to 30% in the visible light region, the wavelength region of 250nm to 280nm in the deep ultraviolet region, which is most important for the bactericidal effect, selectively shows a high reflectance of more than 85%. An example of forming the same protective film with a film thickness of 47μm on an aluminum substrate is shown in the dotted line. Figure 3It can be seen that the reflectivity of the aluminum substrate also comes from the reflectivity of the substrate itself, but compared with the reflectivity of 60% to 80% in the visible light region, it selectively shows a high reflectivity of more than 90% in the wavelength region of 250nm to 280nm. Figure 4 This is an enlarged view of the reflectance spectrum of sample No. 2 in the deep ultraviolet region, and it is found that the reflectance is as high as 85% or more in the wavelength region of 250 nm to 280 nm.
[0067] Figure 5 The reflectance spectra of the deep ultraviolet region of samples No. 16 and No. 17 show that the reflectance is high at 85% or more in the wavelength region of 250nm to 280nm, but when the content of zirconium oxide powder increases, the influence of aggregation begins to appear, and although the reflectance on the long wavelength side increases, the reflectance on the short wavelength side decreases. When the content of zirconium oxide powder reaches 50wt%, the reflectance at 250nm becomes 85%.
[0068]
Explanation of symbols
[0069] 1 Electrode
[0070] 2. Encapsulation resin
[0071] 3 Deep UV LED chips
[0072] 4 Gold Thread
[0073] 5. Protective film
[0074] 6 metal substrate
[0075] 7 Silicone
[0076] 8 Zirconia powder
Claims
1. A photoresist ink comprising silicone and 32 wt % to 37 wt % of zirconium oxide powder having an average particle size D50 of 0.5 μm to 1 μm, When the photoresist ink is coated on a substrate with a film thickness of 30 μm or more and 100 μm or less and cross-linked and cured, the diffuse reflectivity in the wavelength range of 250 nm to 280 nm is 85% or more. 2 . The photoresist ink as claimed in claim 1 , wherein after being irradiated with deep ultraviolet light of a wavelength of 265 nm for 1000 hours, the reflectivity of the photoresist ink at a wavelength of 265 nm decreases to less than 5%.
Citation Information
Patent Citations
Glass ceramic composition and light emitting device
JP2011246329A
Manufacturing method of LED substrate
JP2012227292A
Luminous body holding substrate and manufacturing method therefor
JP2014187158A
Substrate for deep UV light-emitting element, coupling substrate for deep UV light-emitting element, and deep UV light-emitting device
JP2017117982A
LED module
JP2019125683A